Orienteering without physical flags or QR codes: Analysis of the Orienteering GPS app - Fraile, Juan; Orgaz-Rincón, Daniel; Ruiz-Bravo, Patricia; Baena-Extremera, Antonio; Fuentesal-García, Julio; Zamorano-Sande, David (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Orienteering is a booming sport within the physical activities in the natural environment and is included in the curriculum of Physical Education (PE). It is an excellent activity from a didactic point of view because it does not need to be competitive, it is challenging, cooperative, inclusive, accessible, and there is a possibility of success for all participants. Although orienteering is the most taught content within these activities, teachers identify barriers that make it difficult to carry it out or improve its practice. This study analyzed the GPS Orienteering app, whose main feature is that there is no need to place physical flags or QR codes. A total of 85 students of the degree in Physical Activity and Sport Sciences, in the subject related to physical activities in the natural environment, experienced a learning progression of orienteering, including the use of this app, of which their perceptions and use were explored. In conclusion, the app is user-friendly and practical, efficiently organizing a race and generating valuable data without requiring flags or QR codes.